The Effect of Islamic Social Reporting and Profitability on Firm Value in Islamic Banks - Putri, Mazaya Qudsya; Roziq, Ahmad; Mahardiyanto, Agus (JIES : Journal of Islamic Economics Studies, 2026)
This study aims to examine the effect of Islamic Social Reporting (ISR) and profitability on firm value in Islamic banks in Indonesia during 2019–2024. This research employs an explanatory quantitative approach using panel data obtained from annual reports of Islamic banks. Profitability is measured using a composite index of Return on Assets (ROA) and Return on Equity (ROE) reduced through Principal Component Analysis (PCA). Firm value is proxied by a modified Tobin’s Q adjusted for non-listed banking characteristics. The analysis applies a panel data regression using the Fixed Effect Model (FEM). The findings indicate that ISR has a positive and significant effect on firm value. Profitability also positively affects firm value. This study contributes to the ISR literature by integrating a composite profitability measure and provides managerial implications for strengthening Islamic bank reputation and performance.